2006
DOI: 10.1177/1465116506060910
|View full text |Cite
|
Sign up to set email alerts
|

Committee Representation in the European Parliament

Abstract: A B S T R A C TThe European Parliament (EP) possesses a highly specialized committee system, operating in a complex institutional and political environment, yet little empirical work has investigated how MEPs are assigned to EP committees and what consequences this process has for representation and policy-making. In this article I examine the growth of EP committees and committee membership since 1979, and address the question of whether these committees are representative of the EP as a whole. Using an origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(111 citation statements)
references
References 16 publications
4
105
0
2
Order By: Relevance
“…This finding was confirmed in a later study by McElroy (2006). Examining the EP's conciliation delegation, Rasmussen (2008a) has also recently shown that the ideological positions of the delegates are generally in line with the EP party groups.…”
Section: Legislative Organizationmentioning
confidence: 62%
“…This finding was confirmed in a later study by McElroy (2006). Examining the EP's conciliation delegation, Rasmussen (2008a) has also recently shown that the ideological positions of the delegates are generally in line with the EP party groups.…”
Section: Legislative Organizationmentioning
confidence: 62%
“…Research on committee assignments outside the US initially focused primarily on the European Parliament (e.g. McElroy, 2006;Whitaker, 2005;Yordanova, 2009) and relied heavily on the congressional framework. With regard to national parliaments, a number of empirical studies argued that committee assignments are based on electoral rules or candidate selection procedures (Crisp, Escobar-Lemmon, Jones, Jones, & Taylor-Robinson, 2009;Stratmann & Baur, 2002).…”
Section: An Overview Of Empirical Committee Researchmentioning
confidence: 99%
“…To identify the relevance of situational variables, we conducted qualitative interviews with the main actors of debate [58] [59,60]). Due to increasing workload, the decision-making process has been rationalized and the working load divided among the members ( [61]).…”
Section: Situational Variablesmentioning
confidence: 99%